2010
DOI: 10.3109/00365548.2010.526956
|View full text |Cite
|
Sign up to set email alerts
|

Emerging transmitted drug resistance in treatment-naïve human immunodeficiency virus-1 CRF06_cpx-infected patients in Estonia

Abstract: Human immunodeficiency virus (HIV)-1 transmitted drug resistance in the drug-naïve population is of growing relevance in Estonia, where the number of antiretroviral (ARV) treatment-experienced subjects has been exponentially increasing during the last 10 y. The aim of this study was to estimate the rate of transmitted drug resistance among newly diagnosed subjects in Estonia in 2008. Genotypic resistance testing for viral genomic RNA was conducted for 201 subjects tested HIV-positive between 1 April and 30 Nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…9 All diagnostic and resistance testing methods in the previous and in the present study were similar. The failure rate of the resistance testing was 28% in 2008.…”
Section: Accordingsupporting
confidence: 67%
See 2 more Smart Citations
“…9 All diagnostic and resistance testing methods in the previous and in the present study were similar. The failure rate of the resistance testing was 28% in 2008.…”
Section: Accordingsupporting
confidence: 67%
“…9 The reanalysis of sequences revealed that the TDR level was 5.5% (95% CI 1.8; 9.24). The available demographic, clinical, TDR mutation, and interpretation of data of TDR mutation-possessing subjects are presented in Table 3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…53,54 Recent pol region analysis showed that the subtype structure of the Estonian HIV epidemic remained unchanged up to 2008. [56][57][58] Drug resistance mutations of HIV were investigated in Estonian treatment naive populations in 2005-2006 and 2008. [56][57][58] These studies indicated that CRF06_cpx and its recombinant forms with subtypes A1 possess several naturally occurring polymorphisms in the protease region (K14R, M36I, H69K, and L89M), also characteristic to other non-B subtype epidemics.…”
Section: Hiv Molecular Epidemiologymentioning
confidence: 99%
“…58 Yet a rapid increase to a 5.5% prevalence of these mutations was detected in samples collected from newly diagnosed HIV patients in 2008--in eight samples drug resistance mutations to the three most widely used antiretroviral drug classes (PI, NNRTI, and NRTI) were detected and three strains possessed mutations determining resistance to at least two antiretroviral classes. 58 These results are slightly above the threshold considered critical for implementation of pretreatment drug resistance testing according to the ''Guidelines for the Use of Antiretroviral Agents in HIV-1-Infected Adults and Adolescents.'' 59 A third integrase region genotyping study has detected several drug resistance-associated polymorphisms (V72I, L74I, V201I, and T206S), but no primary drug resistance mutations against integrase inhibitors.…”
Section: Hiv Molecular Epidemiologymentioning
confidence: 99%